Noncentrifugal activation patterns in focal RVOT PVC/VT: New insights from high density multielectrode mapping. (4th November 2020) - Ng, Justin; Chhachhi, Binita; Stobie, Paul; Keren, Arieh; Popal, Sohail; Reichlin, Tobias
Abstract: Background: Activation from an automatic focus is thought to show centrifugal spread. In patients with premature ventricular complex/ventricular tachycardia (PVC/VT) from the right ventricular outflow tract (RVOT), the presence of preferential conduction and epicardial connections could however also lead to noncentrifugal wavefront propagation. Objective: To study endocardial activation in RVOT PVC/VT using high‐resolution 3D activation mapping. Methods: Consecutive patients with frequent idiopathic PVC/VT were studied. High‐resolution 3D activation maps were acquired using a multielectrode mapping catheter (Orion, Rhythmia, Boston Scientific). Noncentrifugal activation was defined as a pattern of wavefront propagation which does not show uniform propagation in all directions from one focus. Patients without sustained ablation success and patients with a left‐sided PVC origin or with insufficient map density were excluded from the analysis. Results: Sixteen patients (44% female) with a median age of 54 years (interquartile range [IQR], 47–64) and a median PVC burden of 19% (IQR, 15–27) were studied. High‐resolution activation maps consisting of a median number of 1863 mapping points (IQR, 1195–2463 points) demonstrated a centrifugal activation in 6/16 (38%) and a noncentrifugal activation in 10/16 (62%). When comparing patients with centrifugal and noncentrifugal activation, patients with centrifugal activation were older ( p  = .01), but no differences were found in age, gender, QRS duration of the PVC's and sites of origin in the RVOT. No procedural complications occurred. Conclusions: High‐resolution multielectrode mapping demonstrates the presence of noncentrifugal activation patterns in some of the patients with idiopathic RVOT PVC/VT. This may indicate the presence of preferential conduction and or epicardial/intramural connections in the outflow tract.